2007
DOI: 10.4028/www.scientific.net/msf.561-565.447
|View full text |Cite
|
Sign up to set email alerts
|

A 21st. Century Perspective on Molybdenum Powder Production by Hydrogen Reduction

Abstract: High purity molybdenum metal powder is produced commercially from hexavalent molybdenum precursors, viz.: ammonium dimolybdate (ADM) or molybdenum trioxide. One conventional process incorporates first-stage and second-stage flowsheet components, with hydrogen gas serving as reductant. This two-stage strategy is employed in order to minimize the formation of volatile molybdenum species that would otherwise be generated at the high temperature required to obtain molybdenum (Mo) in a single stage conversion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In practical, reduction of MoO 3 powders by hydrogen is one of the most used methods to obtain metallic molybdenum with high purity. 53 Therefore, hydrogen should play an essential role in determining the structure of the metallic Mo catalyst. Generally, the activity of catalysts was always affected by their surface structures and compositions.…”
Section: Wulff Particles Of the Mo Catalystmentioning
confidence: 99%
“…In practical, reduction of MoO 3 powders by hydrogen is one of the most used methods to obtain metallic molybdenum with high purity. 53 Therefore, hydrogen should play an essential role in determining the structure of the metallic Mo catalyst. Generally, the activity of catalysts was always affected by their surface structures and compositions.…”
Section: Wulff Particles Of the Mo Catalystmentioning
confidence: 99%
“…Molybdenum (Mo) is a typical refractory metal with many special properties, such as high temperature strength, low thermal expansion coefficient and high Young's modulus [1,2]. In recent years, many studies have shown that using Mo thin films to replace or as barrier layers of Ag, Cu and Al thin films can effectively improve the conductivity, anti-electro migration and thermal stability of thin film electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum (Mo) is a typical refractory metal with many special properties, such as high temperature strength, low thermal expansion coefficient and high Young's modulus. So, it is widely used in many fields, for examples, electronics, aerospace, energy and lighting [1][2][3][4]. In recent years, studies show that using Mo thin films to replace or as barrier layers of Ag, Cu and Al thin films can effectively improve the conductivity, anti-electromigration and thermal stability of thin-film electrode .…”
Section: Introductionmentioning
confidence: 99%